1982
DOI: 10.1073/pnas.79.15.4642
|View full text |Cite
|
Sign up to set email alerts
|

Synexin facilitates fusion of specific phospholipid membranes at divalent cation concentrations found intracellularly.

Abstract: The effect of synexin (an adrenal medullary protein) on the kinetics of Ca2+-and Mg2"-mediated membrane fusion was examined. Membrane fusion was studied by monitoring intermixing of-the aqueous contents of phospholipid vesicles. Synexin 'facilitated Ca2+-mediated, but not Mg2+-mediated, fusion of phosphatidate/phosphatidylethanolamine (1:3) and phosphatidate/phosphatidylserine/phosphatidylethanolamine/cholesterol (1: 2: 3:2) vesicles. The threshold concentration of Ca2+ for fusion was decreased to 10 jM in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…Isolation and purification of chromaffin granules were performed as described by Brocklehurst and Pollard (61). Large unilamellar PS liposomes ("LUV") were prepared by the swelling method (62) and fusion analyzed (55,56 (1996) tated synexin was then assayed for bound nucleotides, as described (68).…”
Section: Methodsmentioning
confidence: 99%
“…Isolation and purification of chromaffin granules were performed as described by Brocklehurst and Pollard (61). Large unilamellar PS liposomes ("LUV") were prepared by the swelling method (62) and fusion analyzed (55,56 (1996) tated synexin was then assayed for bound nucleotides, as described (68).…”
Section: Methodsmentioning
confidence: 99%
“…Several years ago Papahadjopoulos and colleagues [13][14][15][16] showed that synexin could fuse liposomes prepared from phosphatidylethanolamine (PE) and phosphatidylserine (PS). However, synexin could only bind to and aggregate phosphatidylinositol (PI) liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…One fruitful approach to this problem has been to study proteins such as synexin, which fuse certain natural and artificial membranes in a calciumdependent manner (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Recently, bovine synexin has been shown to generate classical capacitative gating currents in isolated acidic phospholipid bilayers (12) and to exhibit exquisitely selective, voltage-sensitive calcium channel activity in similar membranes (13).…”
mentioning
confidence: 99%